Factors influencing research activities of postgraduate students in the University of Mazandaran, Iran / Nader Razeghi - Razeghi, Nader (Universiti Teknologi MARA, 2019)
Postgraduate student’s academic activities have an important role in the production and development of scientific knowledge. The present study was mainly aimed at identifying factors which might affect postgraduate students’ scientific and research activities at Mazandaran University. The survey method was used and the data were collected through questionnaire. The sample population was selected through stratified sampling method and consisted of 278 postgraduate students doing their masters and PhD study. The findings of the study showed that there was not a significant difference between the scientific activities of doctoral and master students in terms of gender, marital status and locality. Beta coefficients indicated that the academic activities of the students were affected most by the university facilities (β=0.36) and students’ satisfaction with the teachers (β=0.34) and the least (β=0.17) by students’ interaction with professors. Additionally, it can be argued based on MIMIC Model that the students’ concerns, as a variable, had a negative impact on their scientific and research activities. The Adjusted R Square indicated that 38% of the scientific and research activities (the dependent variable) were explained by the independent variables studied in the model.